Pdf-Based Digital Comic Innovation Class V Human Respiratory System Material - Rahayuningsih, Hasanah Febriyanni; Setiawan, Deni (Postgraduate, University of Mataram, 2023)
This research is motivated by the limitations of learning media in science learning content, so students need help understanding the material. This study aims to examine the feasibility and test the effectiveness of PDF-based digital comic media material on the human respiratory system. This type of research is Research and Development (R&D) with the Borg and Gall development model. The subjects of this study were fifth-grade students at SD Negeri 2 Pagersari with 36 students. Data collection techniques using observation, interviews, documentation, questionnaires, and tests. Data analysis techniques use product feasibility and initial and final data analysis (t-test and N-gain test). The research results show that; (1) it is appropriate to use the percentage of material experts and media experts who get percentages of 87% and 100%, as well as teacher and student responses of 97% and 93%; (2) it is effective in increasing student learning outcomes with the results of the t-test showing a significance value (Sig.) of the variable results of the Pretest and Posttest in class V SD Negeri 2 Pagersari is 0.001, so H0 is rejected. At the same time, the results of the N-gain test analysis showed 64.526 with the medium criteria category. This study concludes that PDF-based digital comic media has proven to be feasible and effective as a learning medium and can improve science learning outcomes on the material of the human respiratory system for class V SD Negeri 2 Pagersari.